Reputation through artificial intelligence? On the effectiveness of virtual influencers as spokespersons in corporate crisis communication - Olbermann, Zoe; Nagl, Magdalena (Frontiers in Communication, 2025)
With virtual social media influencers, a new form of brand ambassador has established itself on social networks. In our study, we look at the extent to which they are also suitable as spokespersons after a corporate crisis. To this end, we conducted a three-stage single-factor design online experiment (N = 169) and compared human influencers with two types of virtual influencers: humanized virtual influencers and animated virtual influencers. Our results show that the two types of virtual influencers differ only in their visual - but not in their mental - human-likeness. The perceived human-likeness triggers a chain of psychological processes - which ultimately has a positive effect on the acceptance of crisis communication and thus on the brand image. In our study, we refer to the limitations of our study and thus classify the knowledge gained. The results underline the complexity but also the necessity of investigating artificial intelligence in brand and corporate communication.